Resposta emocional dos consumidores a estímulos informativos, empáticos e sociais em comunicação de marketing pró-consciência do bem-estar animal - Mariana Marinho da Costa Lima Peixoto (2022)
The human species creates values and beliefs regarding the adoption of animals for various purposes, such as protection and safety, work, companionship and affection, direct food and by-products, entertainment, research production, medicines and cosmetics, among others. In a basic cut, the awareness of values by humans regarding animal welfare is one of the major factors in consumer emotions and behavior. The objective of this thesis was to measure the antecedent beliefs of behavioral intention and the relationship between self-reported emotions and somatic emotions of consumers facing marketing communication actions with informative, empathetic and social stimuli for an awareness of animal welfare. From a literature review, it was possible to identify that information, empathy, and social influence are constructs that can stimulate animal welfare awareness in consumers and, consequently, their behavioral intention to consume, thus constituting a theoretical-empirical framework. The methodology defined for the study has a quantitative approach and was carried out in two phases. Phase 1 comprised a non-experimental exploratory study by means of a survey to identify the salient beliefs of the Theory of Planned Behavior and to validate the instruments used in the experimental treatment by means of a manipulation check. Phase 2 comprised experimental research. A betweensubject design, with the subjects divided into 3 experimental groups and 1 control group, was carried out to test the effects of marketing communication to raise awareness of animal welfare, through advertising pieces with informative, empathetic, and social stimuli, on emotion and as a proxy for consumers' behavioral intention. The treatment consisted in showing videos whose selection criteria were based on the ADF (accessibility, desirability, and feasibility) framework, so that the videos contemplated the dimensions of accessibility, desirability, and feasibility as strategies of advertising persuasion. The participants' facial expressions were captured during the watching of the videos to obtain somatic responses and infer primary emotions, and the PANAS scale measured cognitive responses before and after treatment, which allowed comparative analyses within and between groups. Data were entered into IBM SPSS software for statistical analyses and FaceReader for emotion analysis, and beliefs were also analyzed using content analysis. The results showed that consumers share the same beliefs regarding animal welfare as food, and that the informational, empathetic, and social stimuli for animal welfare awareness induced facial expressions that inferred negative emotions, specifically sadness. Furthermore, the results of the physiological measurement of emotions by FaceReader did not correlate with those of the self-reported measurements on the PANAS. Although there is some literature on the topic, no studies on marketing communication actions that encourage animal welfare awareness for emotion inference were identified. Thus, this experimental study established a successful interdisciplinary empirical theoretical link between the fields of Management and Neuroscience, thus contributing to the fields of applied social and behavioral sciences.